Epitaxial lateral overgrowth of AlN on self-assembled patterned nanorods. Issue 2 (24th November 2014) - Conroy, Michele; Zubialevich, Vitaly Z.; Li, Haoning; Petkov, Nikolay; Holmes, Justin D.; Parbrook, Peter J.
Abstract : We report an inexpensive nanoscale patterning process for epitaxial lateral overgrowth (ELOG) in AlN layers grown by metal organic vapour phase epitaxy (MOVPE) on sapphire. Abstract : We report an inexpensive nanoscale patterning process for epitaxial lateral overgrowth (ELOG) in AlN layers grown by metal organic vapour phase epitaxy (MOVPE) on sapphire. The pattern was produced by an inductively coupled plasma etch using a self-assembled monolayer of silica spheres on AlN as the lithographic mask. The resulting uniform 1 μm length rod structure across a wafer showed a massive reduction in threading dislocations (TDs) when annealed at 1100 °C. Overgrowing homoepitaxial AlN on top of the nanorods, at a temperature of 1100 °C, produced a crack free coalesced film with approximately 4 μm of growth, which is formed at a much lower temperature compared to that typically required for microscale ELOG. The improved crystal quality, in terms of TD reduction, of the AlN above the rods was determined by detailed weak beam (WB) electron microscopy studies and showed that the threading dislocation density (TDD) was greatly reduced, by approximately two orders of magnitude in the case for edge-type dislocations. In situ reflectance measurements during the overgrowth allowed for thickness coalescence to be estimated along with wafer curvature changes. The in situ measurements also confirmed that tensile strain built up at a much slower rate in the ELOG AlN layer compared to that of AlN prepared directly on sapphire.